A correction to a recent review of the genus Hemidactylus Goldfuss, 1820 (Squamata: Gekkonidae) from Angola, with the description of two additional species - Ceríaco, Luis M. P.; Agarwal, Ishan; Marques, Mariana P.; Bauer, Aaron M. (Zootaxa, 2020)
A correction to the recent revision of the genus Hemidactylus Goldfuss, 1820 from Angola is presented. The previous revision assigned some historical specimens to H. bayonii and H. nzingae, with one specimen even being considered a paratype of the latter taxon. A review of the morphological data of all of the specimens used in the previous study found that two other undescribed taxa, morphologically similar to H. bayonii and H. nzingae, respectively, were overlooked. We here present a re-description of these specimens and provide the diagnostic characters that allow their recognition as two new species, both endemic to Angola. In order to provide an accurate picture of the diversity of Hemidactylus in the country and to correct our previous misidentifications that could lead to some taxonomic instability, we herein describe H. hannasabinae sp. nov. and H. vernayi sp. nov.